2004
DOI: 10.1088/1475-7516/2004/12/005
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational clustering of relic neutrinos and implications for their detection

Abstract: Abstract. We study the gravitational clustering of big bang relic neutrinos onto existing cold dark matter (CDM) and baryonic structures within the flat ΛCDM model, using both numerical simulations and a semi-analytical linear technique, with the aim of understanding the neutrinos' clustering properties for direct detection purposes. In a comparative analysis, we find that the linear technique systematically underestimates the amount of clustering for a wide range of CDM halo and neutrino masses. This invalida… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
340
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(357 citation statements)
references
References 118 publications
16
340
0
1
Order By: Relevance
“…211802-2 of origin is about 10 ÿ4 eV 2 , 10 ÿ5 eV 2 , and 10 ÿ6 eV 2 for 8 B, 7 Be, and pp neutrinos, respectively. With our choice of jM 2 i j of O 10 ÿ5 ÿ 10 ÿ4 eV 2 at neutrino production, we expect nonstandard matter effects to be of the same order as standard matter effects.…”
Section: 211802 (2005) P H Y S I C a L R E V I E W L E T T E R S mentioning
confidence: 99%
“…211802-2 of origin is about 10 ÿ4 eV 2 , 10 ÿ5 eV 2 , and 10 ÿ6 eV 2 for 8 B, 7 Be, and pp neutrinos, respectively. With our choice of jM 2 i j of O 10 ÿ5 ÿ 10 ÿ4 eV 2 at neutrino production, we expect nonstandard matter effects to be of the same order as standard matter effects.…”
Section: 211802 (2005) P H Y S I C a L R E V I E W L E T T E R S mentioning
confidence: 99%
“…(10), does not consider clustering of neutrinos on CDM structures, which occurs when the neutrino thermal velocity drops below the velocity dispersion, v, of forming clusters; for instance, it takes place at z ∼ 2.3 for v ∼ 1000 km s −1 and m ν ∼ 0.5 eV. The corresponding neutrino halo profile is flatter in the centre than a pure CDM Navarro-Frenk-White (Ringwald & Wong 2004). Including it in the 1-halo term of the halo model, Abazajian et al (2005) showed that it decreases the non-linear matter power spectrum.…”
Section: Robustness Of the Constraintsmentioning
confidence: 99%
“…Gravitational clustering is most significant for more massive neutrinos, since these became non-relativistic at earlier times. Simulations show that the local density of neutrinos could be enhanced over the cosmological average by an order of magnitude or more [8,9].…”
mentioning
confidence: 99%